Isoorientin Attenuates Cisplatin-Induced Nephrotoxicity Through the Inhibition of Oxidative Stress and Apoptosis via Activating the SIRT1/SIRT6/Nrf-2 Pathway - Fan, Xiaoye; Wei, Wei; Huang, Jingbo; Liu, Xingkai; Ci, Xinxin (Frontiers in Pharmacology, 2020)
Cisplatin (CDDP) is a widely used chemotherapeutic agent for various solid tumors, but its severe side effects, particularly nephrotoxicity, limit its clinical application. Isoorientin (Iso) is a well-known flavonoid-like compound that has been shown to have antioxidant effects. However, the effect of Iso on CDDP-induced nephrotoxicity has not yet been elucidated. We assessed the effects of Iso against CDDP-induced nephrotoxicity in vitro using mTEC cells and further explored the mechanisms underlying CDDP-induced renal dysfunction in vivo in wild-type and Nrf2-/- mice. The results showed that Iso treatment significantly reduced CDDP-induced nephrotoxicity via attenuating cell damage in vitro and via ameliorating renal injury, as determined by biochemical markers, in mice. The molecular mechanism underlying this protection was also investigated. Iso upregulated SIRT1 and SIRT6 expression in vivo and in vitro. In addition, Iso activated Nrf2 translocation and the expression of its downstream antioxidant enzymes HO-1 and NQO1, whereas it inhibited NOX4 expression, thus decreasing oxidative stress. Notably, the protective effects of Iso observed in wild-type mice were completely abolished in Nrf2-/- mice. Collectively, these data indicate that the protective effect of Iso on CDDP-induced nephrotoxicity by SIRT1- and SIRT6-mediated Nrf2 activation regulates oxidative stress, inflammation and apoptosis. The absence of Nrf2 exacerbates CDDP-induced renal damage, and the pharmacological activation of Nrf2 may represent a novel therapy to prevent kidney injury.